2005
DOI: 10.1080/14767050500139604
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of elective induction of labor with favorable Bishop scores versus expectant management: A randomized clinical trial

Abstract: In women with favorable Bishop scores, elective induction of labor resulted in no increase in cesarean delivery compared to expectant management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 3 publications
1
79
0
Order By: Relevance
“…4,15,16 A Cochrane review from 2012 also suggested no increase in newborn asphyxia with an earlier birth induction practice. 8 Although the decrease in asphyxia may have been reflected in fewer Apgar scores < 7 at 5 minutes, this outcome was also influenced by a range of other factors, such as drug use, trauma, congenital abnormalities and infections, problems that have not been resolved by an earlier labour induction policy.…”
Section: Discussionmentioning
confidence: 99%
“…4,15,16 A Cochrane review from 2012 also suggested no increase in newborn asphyxia with an earlier birth induction practice. 8 Although the decrease in asphyxia may have been reflected in fewer Apgar scores < 7 at 5 minutes, this outcome was also influenced by a range of other factors, such as drug use, trauma, congenital abnormalities and infections, problems that have not been resolved by an earlier labour induction policy.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Similarly, Gelisen O et al in 2007 also reported 4.3% of babies were admitted in NICU among induced patient but another study done by Nielsen P et al in 2005 reported that there was no NICU admission of baby in induced group. [27,28] Peters M in 1995 reported 1% of neonatal death in induction groups. [29] Lampe LG also reported 0.05% of neonatal death in contrast to Praysak M who reported that there was no neonatal death in induced patients.…”
Section: Indications For Inductionmentioning
confidence: 99%
“…However, these studies all focused on women with already established problems such as oligohydramnios (52), macrosomia (53), and insulin dependent diabetes (54). In addition, several often-cited randomized clinical studies that did not find benefit with labor induction either took place before the availability of prostaglandin cervical ripening protocols or were not sufficiently powered to fully evaluate the full spectrum of birth outcomes (55)(56)(57)(58). The prospective trials that have demonstrated improvement in birth outcomes related to labor induction were studies of women with mild-moderate risk profiles where labor induction was employed before the development of a recognized complication (59)(60)(61).…”
Section: Commentmentioning
confidence: 99%